Pengembangan Media Pembelajaran berbasis Nearpod Mata Pelajaran Fikih Materi Mawaris - Muna, Faizul; Nasution, Khoiruddin; Hasyim, A Dardiri (Fahima, 2025)
The rapid advancement of technology facilitates the learning process for students. One of them is by using technology-based learning media. In this research, a Nearpod-based blended learning media for Jurisprudence subject is developed, focusing on mawaris material. This learning media includes a summary of the material and practice questions which are all available in the Nearpod media that has been developed. The purpose of this study is to develop a valid and readable Nearpod-based blended learning media. This research is an RnD (Research and Development) study. This research applies the ADDIE development model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 32 XII grade students at MA Nahjatus Sholihin. The data collection techniques used were interviews and questionnaires. This research data includes qualitative and quantitative data. Qualitative data were obtained from interviews at the analysis stage, while quantitative data were obtained from the results of the readability questionnaire. The results of this study indicate that the media readability questionnaire meets very valid criteria, with a score of 87.5%. This media makes it easier for students to understand mawaris material and increase student interest in learning.